2019
DOI: 10.1037/ort0000390
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the indirect effect of alcohol expectancies on ethnic identity and adolescent drinking outcomes.

Abstract: Although overall rates of alcohol use tend to be lower among racial/ethnic minority youth compared to White youth, consequences associated with use tend to be more severe. Identifying factors that prevent alcohol use is crucial to reducing its impact among minority adolescents. One such factor is ethnic identity, which involves gaining clarity about one’s ethnic background and regard toward one’s ethnic group. Strong ethnic identity has been found to work through antidrug beliefs to decrease minority youth’s s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…For adolescents, a final score of 4 is a cutoff for alcohol abuse or dependence (Knight et al, 2003 ). Reliability of AUDIT has been supported by research on adolescents aged 12–18 years old self-identified as black (70%), Latinx (15%), multiracial (12%), and Indigenous (3%) (Cronbach’s alpha = 0.91; Banks et al, 2019 ). The scale had good inter-item reliability (Cronbach’s alpha = 0.87 for the total sample, 0.82 for Asian, 0.92 for black, 0.91 for Indigenous, 0.88 for Latinx) for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…For adolescents, a final score of 4 is a cutoff for alcohol abuse or dependence (Knight et al, 2003 ). Reliability of AUDIT has been supported by research on adolescents aged 12–18 years old self-identified as black (70%), Latinx (15%), multiracial (12%), and Indigenous (3%) (Cronbach’s alpha = 0.91; Banks et al, 2019 ). The scale had good inter-item reliability (Cronbach’s alpha = 0.87 for the total sample, 0.82 for Asian, 0.92 for black, 0.91 for Indigenous, 0.88 for Latinx) for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…19 In these cases, Black students may be more likely to endorse negative AOEs than positive ones. 23 Overall, 64% of first-year college students' hookups involved alcohol consumption. 24 Black college students are less likely to hookup than their White counterparts, 25 thus underscoring the importance of understanding Black college students' AOEs specific to sexual behaviors and perceptions of intimacy.…”
Section: Black College Students' Aoesmentioning
confidence: 99%
“…For example, in the study by Paulus et al (2019), the level of emotion dysregulation among Latinx moderated the association between acculturative stress and alcohol use. Banks et al (2019) found that ethnic identity and type of drug expectancy predicted decreased alcohol consumption. While Paulus et al and Banks et al used person variables, the work of Vaeth and his colleagues (Vaeth, Caetano, & Canino, 2019) tested a mediation model involving molar variables such as neighborhood disadvantage and neighborhood social cohesion.…”
Section: What Have We Learned From the Research?mentioning
confidence: 99%
“…When comparing the alcohol between various Asian American college students, Iwamoto et al found that risk factors within Asian Americans included American born status (vs. overseas born), drinking to cope, and being members of fraternities or sororities. Banks, Winningham, Wua, and Zapolskia (2019) studied the association between ethnic identity and negative drug expectancies on rates of alcohol consumption. Having a strong ethnic identity helped to prevent alcohol use.…”
Section: What Have We Learned From the Research?mentioning
confidence: 99%